Intra and interspecific vegetative variability of Astrocaryum chonta and A. javarense (Arecaceae) from Jenaro Herrera, Loreto, Peru - Machahua, Miguel (2014)
Vegetative quantitative characters from adult, juvenile II, juvenile I and seedlings of Astrocaryum chonta and Astrocaryum javarense for four populations of Jenaro Herrera were analyzed in order to observe the patterns of vegetative variation at intra and interspecific level. The biometric data were analyzed using ANOVA (p<0.05 and 0.01). At intraspecific level the 37% and 64% of vegetative characters are significantly different in Astrocaryum chonta and Astrocaryum javarense, while at interspecific level the 81% are significantly different.